(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Metabolic syndrome is a cluster of metabolic abnormalities including central obesity, hypertension, dyslipidemia, and hyperglycemia that significantly increase the risk of cardiovascular disease and type 2 diabetes mellitus. The prevalence of metabolic syndrome is increasing in rural populations due to changing lifestyle patterns and reduced physical activity. This study aimed to determine the prevalence of metabolic syndrome and its components among adults in a rural community. Methodology: This community-based cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2024 to October 2025. A total of 250 adults aged 18 years and above were selected using multistage random sampling technique. Data regarding demographic characteristics, lifestyle factors, anthropometric measurements, blood pressure, fasting blood glucose, and lipid profile were collected using a structured questionnaire and standardized procedures. Statistical analysis was performed using SPSS version 25.0, and p <0.05 was considered statistically significant. Results: The prevalence of metabolic syndrome was 56% among the study participants. Central obesity was the most common component (56%), followed by hypertension (48%), dyslipidemia (40%), and hyperglycemia (36%). Education level showed significant association with metabolic syndrome (p <0.05), while age, gender, and occupation were not significantly associated. Lifestyle factors including unhealthy diet, obesity, insufficient sleep, smoking, alcohol consumption, and stress were significantly associated with metabolic syndrome. Conclusion: Metabolic syndrome is highly prevalent among adults in rural communities and is strongly associated with unhealthy lifestyle factors. Early screening and lifestyle modification programs are essential to reduce future cardiovascular and metabolic complications.